Functional Coupling of Cav2.3 and BK Potassium Channels Regulates Action Potential Repolarization and Short-Term Plasticity in the Mouse Hippocampus - Gutzmann, Jakob J.; Lin, Lin; Hoffman, Dax A. (Frontiers in Cellular Neuroscience, 2019)
Voltage-gated ion channels are essential for signal generation and propagation in neurons and other excitable cells. The high-voltage activated calcium-channel Cav2.3 is expressed throughout the central and peripheral nervous system, and within CA1 hippocampal pyramidal neurons it is localized throughout the somato-dendritic region and dendritic spines. Cav2.3 has been shown to provide calcium for other calcium-dependent potassium channels including small-conductance calcium-activated potassium channels (SK), but big-conductance calcium-activated potassium channels (BK) have been thought to be activated by calcium from all known voltage-gated calcium channels, except Cav2.3. Here we show for the first time that CA1 pyramidal cells which lack Cav2.3 show altered action potential (AP) waveforms, which can be traced back to reduced SK- and BK-channel function. This change in AP waveform leads to strengthened synaptic transmission between CA1 and the subiculum, resulting in increased short-term plasticity. Our results demonstrate that Cav2.3 impacts cellular excitability through functional interaction with BK channels, impacting communication between hippocampal subregions.